2019
DOI: 10.1523/jneurosci.1728-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened Inputs from Secondary Motor Cortex to Striatum in a Mouse Model of Compulsive Behavior

Abstract: Hyperactivity in striatum is associated with compulsive behaviors in obsessive-compulsive disorder (OCD) and related illnesses, but it is unclear whether this hyperactivity is due to intrinsic striatal dysfunction or abnormalities in corticostriatal inputs. Understanding the cellular and circuit properties underlying striatal hyperactivity could help inform the optimization of targeted stimulation treatments for compulsive behavior disorders. To investigate the cellular and synaptic abnormalities that may unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 62 publications
8
67
1
Order By: Relevance
“…Interestingly, this positions central striatum (CS) at a crucial nexus of corticostriatal inputs along this topography (Ebrahimi et al, 1992;Oh et al, 2014), making it well suited to link motivational factors and sensorimotor responses. Consistent with this idea, in prior work we demonstrated that CS receives projections from both lateral orbitofrontal cortex (LOFC) and anterior lateral motor area (ALM) (Corbit 2019), regions implicated in behavioral flexibility (Kim and Ragozzino, 2005) and motor preparation (Guo et al, 2014;Li et al, 2015), respectively. Furthermore, early studies showed that activating central regions of striatum via disinhibition with picrotoxin caused tic-like behavior in rodents (Tarsy et al, 1978).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, this positions central striatum (CS) at a crucial nexus of corticostriatal inputs along this topography (Ebrahimi et al, 1992;Oh et al, 2014), making it well suited to link motivational factors and sensorimotor responses. Consistent with this idea, in prior work we demonstrated that CS receives projections from both lateral orbitofrontal cortex (LOFC) and anterior lateral motor area (ALM) (Corbit 2019), regions implicated in behavioral flexibility (Kim and Ragozzino, 2005) and motor preparation (Guo et al, 2014;Li et al, 2015), respectively. Furthermore, early studies showed that activating central regions of striatum via disinhibition with picrotoxin caused tic-like behavior in rodents (Tarsy et al, 1978).…”
Section: Introductionsupporting
confidence: 77%
“…Prior work has demonstrated that anterior M2/anterior lateral motor area (ALM), one of the major cortical inputs to CS (Corbit et al, 2019), is associated both with appropriate sequencing of movements during trained tasks and with generating licking movements (Bollu et al, 2019;Li et al, 2015;Rothwell et al, 2015). ALM may therefore be uniquely suited for guiding selection of spontaneously generated behaviors such as body grooming.…”
Section: Alm Shows Increased Activity Specifically At Grooming Onsetmentioning
confidence: 99%
See 1 more Smart Citation
“…The opsin ChrimsonR was transduced in either of the two cortical regions and a 625 nm LED implanted above the cortex ( Figure 6A ). In reduced preparations, OFC and M2 have both been found to regulate the activity of neurons in specific DS regions (Corbit et al, 2019) , with the impact of OFC on DS being stronger than that of M2. We sought to confirm these findings in freely behaving mice.…”
Section: Top-down Control Of Dorsal Striatummentioning
confidence: 99%
“…Activation of striatal dopamine D1 receptors induces stereotypies in non-human animals 7 , including those with dopamine deficiency 8 and hyperdopaminergic function 9 , implicating a dysregulated direct-pathway in stereotypy behavior. Similarly, TS and OCD patients display increased sensitivity of striatal dopamine receptors and downregulation of D1 receptors 10,11 likely contributing to striatal hyperactivity 6, 12 . Additionally, mutations in genes regulating synaptic function and dendritic growth occur in TS, OCD and ASD [13][14][15][16][17] and have been confirmed by striatal transcriptome analyses in TS and OCD patients 18,19 . Thus, impaired MSN morphology combined with disrupted physiological properties may underlie neuronal hyperactivity and/or dopamine hypersensitivity and ultimately altered direct pathway output 8 .…”
Section: Introductionmentioning
confidence: 84%